Effectiveness of Fast Interval Training in The Competition Phase on Stamina Level of 800m Runner at Satset Athletic Club - Tio Khalasya; Kardjono; Patriana Nurmansyah Awwaludin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study examined the effectiveness of a short Fast Interval Training (FIT) program during the competition phase on the stamina of 800 meter runners at Satset Athletic Club. A quasi-experimental design with one group was used, involving 15 semiprofessional athletes who had been training regularly for at least six months and were preparing for a regional event. The FIT program lasted three weeks with four sessions each week. Stamina was measured through an 800-meter run before and after the intervention. A paired-sample t-test showed a significant improvement (t = 9.987; p < 0.001). On average, athletes improved their times by 3–4 seconds, representing about a 2.5% increase in performance. These findings suggest that FIT is a practical short-term strategy to prepare athletes during the competition phase, although careful management of recovery is essential.